PENYEBARAN SALAFI JIHADIS KE PERGURUAN TINGGI DI MALAYSIA DAN DAMPAKNYA TERHADAP ISLAMIPHOBIA - Amirulhakim Ahmad Nadzri; Rahimin Affandi Abdul Rahim; Mohd Anuar Ramli; Muhd Imran Abd Razak; Muhammad Yusri Yusof Salleh; Paiz Hassan (JAS-PT (Jurnal Analisis Sistem Pendidikan Tinggi Indonesia), 2018)
Dissemination of Islam is an honourable act that requires a concept or medium which is education. Currently, the higher education institutions has been invated bu Salafi Jihadis ideology which impacted Islam negatively where eventually led to Islamophobic escalation. This research is conducted through literay methodology which analysing this previous research, manuscripts and casa studies that occurred within the society. This research finds that the higher education institutions has been the platform for disseminating salafi jihadis ideology which contributing to Islamophobia. Keyword: Higher Education Institutions, Salafi Jihadis, Islamophobia